Model-based Modified OGTT Insulin Sensitivity Test Design. Issue 27 (2018) - Holder-Pearson, Lui; Bekisz, Sophie; Knopp, Jennifer; Docherty, Paul; Chase, J. Geoffrey; Desaive, Thomas
Abstract: Type 2 diabetes mellitus requires early, accurate, and efficient monitoring for best treatment. Current common diagnosis tools either test late-appearing symptoms, are low resolution, or are expensive in cost and time. A system of physiological models for the oral ingestion of glucose, subcutaneous injection of insulin, and glycaemic control, are used to generate a quantitative test for insulin sensitivity. The proposed test uses 35g of oral glucose, 2.0 units of rapid-acting insulin, and both intra-venous and finger-prick blood samples for insulin, C-peptides, and blood glucose levels frequently over a 2-hour period. The test is developed in silico to enable early and repetitive monitoring of the pathogenesis of type 2 diabetes. In conjunction with emerging technologies in insulin sensing and needle-free delivery and monitoring devices, there is a pathway with this test to provide more effective, efficient early diagnosis of diabetes risk.